Pengaruh Metode Latihan Sport Drajat Rangkaian Latihan Dengan Sport Drajat Rangkaian Bermain terhadap Keterampilan Dasar Petarung - Desi Purnama Sari; Suci nanda sari; Sari Mariati; muhammad fakhrur rozi; Afrizal S Afrizal S (Jurnal Patriot, 2021)
Based on the results of research observations, it turns out that the basic skills of combatants are still low. The low basic technical skills of this fighter is thought to be due to the use of training methods by the coach in coaching. This study aims to reveal the effect of the Play Sequence Method and the Exercise Series Method in Drajat Sport on the Basic Technique Skills of Derajat Fighting Martial Arts. This research method is quasi-experimental (quasi-experimental). The population of this study was 263 people, while the sample was determined by purposive sampling, namely: fighter kurata III. The test used is a quick punch skill test, inner circle punch, outer ring punch and side kick skill test, back kick, inner circle kick which aims to determine the basic technical skills skills of Tarung Derajat martial arts fighters, while the data analysis used is the t-test. . The results of the study showed that: (1) the playing circuit method in the Drajat Sport gave a significant influence on the basic technical skills of the fighters from an average of 54.52 in the pre test to 56.10 in the post test (22.72> 1.729 th) (2) The Exercise Series Method in Sport Drajat has a significant effect on basic technical skills of fighters from an average of 54.59 in the pre test to 56.79 in the post test (th 4.06> tt 1.729). (3) The playing sequence method in Drajat Sport is more effective than the Drajat Sport series method to improve the basic technical skills of Tarung Derajat martial arts fighters (th 8.92> tt 1.734).